2013
DOI: 10.1016/j.jamcollsurg.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

AJCC Cancer Staging Manual 7th Edition Criteria for Colon Cancer: Do the Complex Modifications Improve Prognostic Assessment?

Abstract: Background The seventh edition of the American Joint Committee on Cancer staging system (AJCC-7) includes significant changes for colon cancer (CC), which are particularly complex in patients with stage II and III disease. We used a national cancer database to determine if these changes improved prediction of survival. Study Design The database of the Surveillance, Epidemiology, and End Results (SEER) Program was queried to identify patients with pathologically confirmed stage I-III CC diagnosed between 1988… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(205 citation statements)
references
References 39 publications
6
184
0
1
Order By: Relevance
“…2). The AjCC 2009 statistics showed that only in relatively early stages can surgical resection be conducted on patients with colon cancer (25). Moreover, we found that HCT116 and HT29 colon cancer cells did not express PLD4 (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…2). The AjCC 2009 statistics showed that only in relatively early stages can surgical resection be conducted on patients with colon cancer (25). Moreover, we found that HCT116 and HT29 colon cancer cells did not express PLD4 (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…We found that GULP1 had significantly lower IC 50 values in lower-expression-level cancer cell lines than in higherexpression-level cancer cell lines, and other 4 immune genes turned out to be the reverse (P-value < 0.05 and top 5 ascending order by FDR) ( Table 4 and Supplementary Table 5). This indicates that immune genes expression levels of the cancer cell lines significantly influence the sensitivity of these cell-lines to drugs.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, we compared IC 50 (drug concentration that reduces viability by 50%) values between immune genes that identified for 19 SL genes' higher-expressionlevel and lower-expression-level cancer cell lines for each of the 265 compounds mentioned above. We found that GULP1 had significantly lower IC 50 values in lower-expression-level cancer cell lines than in higherexpression-level cancer cell lines, and other 4 immune genes turned out to be the reverse (P-value < 0.05 and top 5 ascending order by FDR) ( Table 4 and Supplementary Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of this study, the following data were retrieved: tumor location, size, depth of invasion into the rectal wall, total number of lymph nodes/positive lymph nodes, grading of the differentiation, and presence of distant metastases. Cancer staging was assessed following the American Joint Committee on Cancer TNM classi!ication (12) . A cPR was de!ined as the absence of viable tumor cells after a histologic examination of the surgical specimen.…”
Section: Histopathologymentioning
confidence: 99%